DNA polymerase I gene of Saccharomyces cerevisiae: nucleotide sequence, mapping of a temperature-sensitive mutation, and protein homology with other DNA polymerases. - Pizzagalli, A (1988)
A 5600-base pair segment spanning the coding region of the Saccharomyces cerevisiae DNA polymerase I gene was sequenced and found to contain an open reading frame of 1468 codons, corresponding to a polypeptide of Mr 166,794. A pol1 temperature-sensitive mutation, encoding a DNA-polymerase-primase complex with altered stability, has a single base-pair substitution that changes the glycine at position 493 to a positively charged arginine. Protein sequence comparison with other prokaryotic and eukaryotic DNA polymerases reveals three major regions of homology. This observation suggests that certain DNA polymerases might require the conservation of critical amino acid residues for activity.